The atmospheric HCHO budget at Dumont d'Urville (East Antarctica): Contribution of photochemical gas‐phase production versus snow emissions. Issue 23 (12th December 2013) - Preunkert, Susanne; Legrand, Michel; Pépy, Guillaume; Gallée, Hubert; Jones, Anna; Jourdain, Bruno
Abstract [1] HCHO was monitored throughout the year 2009 at the coastal East Antarctic site of Dumont d'Urville (DDU) using Aerolaser AL‐4021 analyzers. The accurate determination of less than 100 pptv required optimization of the analyzers, in particular, to minimize effects of changing ambient temperatures. The impact of station activities and of the presence of large penguin colonies at the site in summer was scrutinized. The obtained contamination‐free record indicates monthly means close to 50 pptv from May to September and a maximum of 200 pptv in January. Zero‐dimensional and 2‐D calculations suggest that in summer, the largest HCHO source is the gas‐phase photochemistry (80%) mainly driven by methane oxidation, which is considerably greater than from snow emissions (20%). The influence of light alkenes, dimethyl sulfide, and halogens remains weak. In winter, snow emissions represent the main HCHO source (70%). These findings are compared to previous studies conducted at the West Antarctic coast. It is shown that in summer the HCHO production from methane chemistry is 3 times more efficient at DDU than at the west coast due to more frequent arrival of oxidant‐rich air masses from inland Antarctica. Halogen chemistry is found to represent a weak HCHO sink at both West and East Antarctica. Compared to DDU, the shallower atmospheric boundary layer and the less efficient gas‐phase production at the west coast make the snow pack the dominant HCHO source (85%) compared to gas‐phase photochemistry (15%) there in summer.